Simultaneous splenectomy improving the outcomes of patients with hepatocellular carcinoma, cirrhosis and portal hypertension treated with hepatectomy. Issue 2 (21st September 2022) - Liu, Fuchen; Guo, Xinggang; Zhang, Wenli; Zou, Minghao; Huang, Jian; Dong, Wei; Zhang, Jinmin; Zhu, Xiuli; Pan, Zeya; Lau, Wan Yee; Zhou, Weiping; Liu, Hui
Abstract: Aims: Patients with cirrhosis and clinically significant portal hypertension (CSPH) usually have concomitant secondary hypersplenism, and splenectomy (Spx) is an option for treating these patients in the Asia‐Pacific region. CSPH is the most important risk factor for postoperative liver dysfunction (PLD) in patients with hepatocellular carcinoma (HCC) and cirrhosis undergoing liver resection. However, the impact of simultaneous Spx and hepatectomy in patients with HCC and CSPH remains unclear. In this study, we aimed to determine the impact of simultaneous Spx on the posthepatectomy outcomes in these patients. Methods: This study included 691 consecutive patients with hepatitis B virus‐related HCC, cirrhosis, and CSPH. These included 565 patients who underwent hepatectomy only (non‐Spx group) and 126 who underwent simultaneous hepatectomy and splenectomy (Spx group). We analyzed the effect of 25 preoperative and 5 intraoperative factors on postoperative outcomes using logistic regression. To overcome any possible selection bias, confounders were balanced by propensity score matching (PSM) and inverse probability of treatment weighting (IPTW) analyses, and subgroup analyses were performed within the PSM‐matched groups. Results: Logistic regression analyses revealed that Spx was an independent protective factor for severe postoperative liver dysfunction (SPLD; odds ratio [OR] = 0.22, 95% confidence interval [CI]: 0.11–0.43, p  < 0.001) and 90‐day SPLD‐related mortality (OR = 0.21, 95% CI: 0.06–0.55, p  = 0.004), respectively. Spx was also independently associated with a higher overall survival rate (hazard ratio = 0.63, 95% CI = 0.47–0.85, p  = 0.002) based on Cox regression analysis. PSM and IPTW models showed that the benefit of Spx was also consistent across the major and minor hepatectomy subgroups examined. Conclusion: Simultaneous Spx improved the outcomes of patients with HCC, cirrhosis, and CSPH treated with hepatectomy, including patients who underwent major and minor hepatectomies. Abstract : Simultaneous splenectomy improved outcomes of HCC patients with cirrhosis and CSPH treated with partial hepatectomy. CSPH, clinically significant portal hypertension; HBV, Hepatitis B virus; HCC, hepatocellular carcinoma; SPLD, severe postoperative liver failure. Key points: Significant findings of the study: This retrospectve study showed simultaneous splenectomy improved the outcomes of patients with HCC, cirrhosis and CSPH treated with hepatectomy. What this study adds: Although simultaneous splenectomy improved the outcomes of patients with HCC, cirrhosis and CSPH treated with hepatectomy, surgical options for such patients still need to be treated with caution and prospectve multi‐institutional randomized studies are also needed.